Bringing the laboratory into the home: A protocol for remote biobehavioral data collection in pregnant women with emotion dysregulation and their infants. (September 2022) - Gao, Mengyu (Miranda); Saenz, Celine; Neff, Dylan; Santana, Marilynn Lape; Amici, Joseph; Butner, Jonathan; Raby, K Lee; Crowell, Sheila E; Conradt, Elisabeth
Pregnant women struggling with emotion dysregulation may be more likely to engage in a wide range of health risk behaviors. This protocol describes a study on intergenerational transmission of emotion dysregulation from the third trimester of pregnancy to 18 months postpartum. Biobehavioral markers of emotion dysregulation are typically measured in laboratory settings which was prohibited by many universities during the COVID-19 pandemic. We describe how markers of emotion dysregulation (e.g. maternal, fetal, and infant heart rate variability) are collected remotely. We detail how data collection can be augmented to reach diverse populations who may not otherwise participate in laboratory-based research.